Pengaruh Partisipasi Anggaran terhadap Senjangan Anggaran dengan Asimetri Informasi, Ketidakpastian Lingkungan, dan Penekanan Anggaran sebagai Variabel Moderasi - Muhammad Reza Rahim; Syamsuri Rahim (Universitas Negeri Malang, 2019)
Abstract: The objective of this study is to examine the influence of budgetary participation on budgetary slack. The moderating effects of information asymmetry, environmental uncertainty and budget emphasis are also being identified on the relationship between budgetary participation and budgetary slack. The population in this study is 27 SKPD (regional working unit) in the government of South Sulawesi Province, with the number of respondents are as many as 105. Research data is collected using census sampling method and analyzed with Moderated Regression Analysis (MRA). The results shows that the budgetary participation has a positive and significant impact on budgetary slack. Meanwhile, the information asymmetry and environmental uncertainty are unable to moderate the relationship between budgetary participation on budgetary slack. In the other hand, budget emphasis is proved to moderate the relationship between the budgetary participation on the budgetary slack.Abstrak: Penelitian ini bertujuan untuk memeriksa dampak dari partisipasi anggaran pada senjangan anggaran. Efek moderasi dari asimetri informasi, ketidakpastian lingkungan dan penekanan anggaran juga diidentifikasi pada hubungan antara partisipasi anggaran dan senjangan anggaran. Populasi pada penelitian ini adalah 27 SKPD di wilayah pemerintahan Provinsi Sulawesi Selatan, dengan total responden berjumlah 105. Data penelitian dikumpulkan menggunakan metode sampling sensus dan dianalisis dengan Moderated Regression Analysis (MRA). Hasil penelitian menunjukkan bahwa partisipasi anggaran memiliki dampak positif pada senjangan anggaran. Sementara itu, asimetri informasi dan ketidakpastian lingkungan tidak dapat memoderasi hubungan antara partisipasi anggaran pada senjangan anggaran. Di sisi lain, penekanan anggaran terbukti memoderasi hubungan antara partisipasi anggaran pada senjangan anggaran.